Alpine research today - Jean-Jacques Brun (Revue de Géographie Alpine)
Alpine research benefits from several international coordination networks, only one of which – ISCAR (the International Scientific Committee on Research in the Alps) – works solely in the Alpine arc. The creation of ISCAR is a consequence of the input and involvement of various Alpine partners around the Alpine Convention. Alpine research now aims to promote an integrated vision of Alpine territories focusing on creating and maintaining spatial and temporal networks of sustainable relationships between humans and the other components of the ecosphere. It combines resource usage with conservation of the biological and cultural diversity that makes up the Alpine identity. This article aims to show: (1) how international Alpine research coordination is organised; (2) the role played by the Alpine Convention as a framework of reference for specifically Alpine research; and (3) the role that the ISCAR international commit-tee and the Interreg “Alpine Space” programmes play in uniting research around territorial challenges relating to biodiversity conservation and territorial development.